Reducing Stoichiometric Excess of Base to Catalytic Amount: Revisiting Staudinger Reaction for β-lactam Synthesis - Yadav, Sonu; Ray, Devalina; Banik, Bimal Krishna (Current Organocatalysis, 2025)
Backgroundβ-lactams have been primarily utilized as a leading class of effective antibiotics. They have been found to show activity against various diseases, prompting the scientific community to prioritise innovative protocols for their synthesis. The general and well-known synthetic strategy involves the classical Staudinger reaction exhibiting [2+2] cycloaddition reaction. However, the protocol utilizes stoichiometric excess of base for efficient product formation.ObjectiveA smarter and more acceptable approach for the synthesis of β-lactams would be to reduce the excess base to a catalytic amount, furnishing a catalytic version of the Staudinger reaction. The modified version can eliminate the hazards arising out of excess use of the base, ultimately promoting the environmentally benign approach.MethodsWith this hypothesis, a base-catalyzed approach in dimethyl formamide (DMF) towards the synthesis of β-lactam via Staudinger reaction has been endorsed under moderate reaction conditions.ResultsThe scope of the substrates was explored with both electron-withdrawing and electron-releasing substitutions in the formation of β-lactam. The reduction of the base amount from stoichiometric to catalytic amount was justified by the involvement of DMF in generating the basic condition for the reaction.ConclusionIt was hypothesized that the decomposition of DMF under the base-catalysed reaction condition can generate dimethylamine, which produces the required basic environment.
Keywords: triethylamine